ANALYSIS OF THE CONTENT MARKETING, INFLUENCER MARKETING, BRAND IMAGE AND PRICE PERCEPTION ON PURCHASE DECISIONS FOR WARDAH SKINCARE PRODUCT ON THE TIKTOK - Maretha , Sindy Diva; Yani , Muhammad; Nugroho , Tofan Tri (International Journal Multidisciplinary (IJMI), 2024)
General Background: Effective digital marketing strategies are crucial for influencing consumer purchasing decisions in the skincare industry. Specific Background: Despite the rise of TikTok as a marketing platform, understanding the relative impact of content marketing, influencer marketing, brand image, and price perception on purchasing decisions remains underexplored. Knowledge Gap: Previous studies have not sufficiently addressed the specific role of these factors within the context of TikTok for skincare products. Aims: This research aims to evaluate the influence of content marketing, influencer marketing, brand image, and price perception on the purchasing decisions of Wardah skincare products on TikTok. Results: Utilizing a quantitative approach with a sample of 100 Wardah skincare buyers and/or TikTok followers, the study reveals that content marketing and influencer marketing do not significantly impact purchasing decisions. In contrast, brand image and price perception have a significant positive effect. Novelty: The study introduces new insights into the effectiveness of TikTok marketing strategies specifically for skincare products and highlights the dominant role of brand image and price perception over content and influencer marketing. Implications: To enhance marketing efficacy, Wardah should focus on optimizing brand image, improving content marketing quality, selecting credible influencers, and employing strategic pricing. This integrated approach will help Wardah strengthen its market position and achieve better consumer engagement in the competitive skincare industry.